PENGARUH SENAM IRAMA TERHADAP KEMAMPUAN MOTORIK KASAR ANAK USIA 5-6 TAHUN DI RA. ROUDHOTUL JANNAH BEKASI TIMUR - Khonita, Nana; Mustofa, Edy; Nabil, Nabil (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2023)
Children aged 5-6 years Early childhood is an individual who is undergoing a process of rapid development, so that children who are still in preschool, a child's gross motor development is needed and must be done, one of which is by using rhythmic gymnastics. Based on the results of observations that researchers have found at RA Roudhotul Jannah, East Bekasi, that the lack of gross motor skills in the development of walking children in place, the lack of development of children in standing on one leg, the lack of development of children in swinging their hands, and the lack of development of children in performing rhythmic gymnastics movements. The purpose of this study was to determine the role of rhythmic gymnastics in improving gross motor skills in motor development and to determine the development of children's gross motor skills after doing rhythmic gymnastics at RA Roudhotul Jannah, East Bekasi. The methodology in this study uses a quantitative approach with a descriptive method. Data collection techniques in this study were carried out through observation and documentation. Based on the results of data collection, it can be concluded that, when learning using rhythmic gymnastics, it can be seen that the gross motor development of children develops or increases every meeting so that children from those who cannot perform simple movements become able. Children also become more excited because of the music so that children become happy and cheerful in doing movements. Therefore, rhythmic gymnastics in children is very instrumental and important so that rhythmic gymnastics must be applied from an early age.